The generation z purchase intention in PLS Coffee Shop - Genoveva Genoveva; Kevin Gideon Nugroho; Filbertha Nathania Kartawaria (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The rapid growth of coffee shops had become a fierce competition, resulting in the number of coffee sales in PLS coffee shop continuing to decline. This competition requires PLS coffee shops to try various ways that will help customers to determine purchase intention. Researchers assume there are 3 factors that could affect customers purchase intention such as product innovation, content marketing, and retail mix. This study is a quantitative research using the multiple regression test that involved 170 generation Z of PLS Coffee Shop as our respondents and used the SPSS analysis technique. The sample was taken using a purposive sample which was distributed randomly around Siwalankerto, Surabaya on 2-16 June 2021. The results of this study prove that product innovation, content marketing, and retail mix applies as an independent variable that effect Purchase Intention. On the other hand, product innovation partially had no effect on purchase intention. However, the hypotheses for content marketing and retail mix are both accepted and have an effect on purchase intention. The content marketing has the biggest contribution to purchase intention (60.2%), therefore, the management could pay attention to the content of marketing. The respondents are generation Z that familiar with the social media, therefore, using the social media as the main promotion tools will maintain the purchase intention.